Translation equivalents of the English articles - Holubová, Hana; Fictumová, Jarmila, 1951-; Masarykova univerzita. Katedra anglistiky a amerikanistiky (2006)
This thesis deals with translation equivalents of English articles into Czech language. It is based on a research on the English-Czech parallel corpus KAČENKA (Korpus anglicko-český-elektronický nástroj Katedry anglistiky) version 1.0, 1998 created by Ing. Mgr. Jiří Rambousek and PhDr. Jana Chamonikolasová from the Department of English and American Studies, the Faculty of Arts, Masaryk University in Brno. The thesis interconnects linguistics and translation, specifically corpus linguistics, grammar and the problem of non-equivalence in translation. It deals with the lexical aspect of the translation of English articles. Two translations of The Jungle Book included in KAČENKA are compared from the point of view of direct translation equivalents of English articles used by the two translators \x{2013} Miloš Maixner and, Hana and Aloys Skoumalovi
Vedoucí práce: Jarmila Fictumová
Diplomová práce (Mgr.)--Masarykova univerzita, Filozofická fakulta, 2006
Keywords: diplomové práce; master's theses